Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Canva terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas VIII SMP Negeri 37 Kota Bekasi - Suryani, Lilis; Hikmawati; Ma’wah, Siti Nurhidayatul; Fajar, Nursita; Megawati, Erna (Lembaga Teewan Journal Solutions, 2026)
This study was motivated by the low exposition text writing skills of eighth-grade students at SMP Negeri 37 Kota Bekasi. Students experienced difficulties in developing ideas, organizing exposition text structures, selecting appropriate diction, and applying proper language rules. In addition, the learning process was still teacher-centered, resulting in low student participation and motivation in writing activities. This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by Canva media on students’ exposition text writing skills. This research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The sample consisted of 64 students divided into an experimental class and a control class. Data were collected through an exposition text writing test and analyzed using normality, homogeneity, and t-tests. The results showed that the average score of the experimental class was 83.00, while the control class obtained an average score of 72.00. The hypothesis testing revealed that the t-value (4.27) was higher than the t-table value (1.999) at the 0.05 significance level. Therefore, the null hypothesis was rejected, and the alternative hypothesis was accepted. It can be concluded that the Problem Based Learning model assisted by Canva media had a significant positive effect on the exposition text writing skills of eighth-grade students at SMP Negeri 37 Kota Bekasi